2016
DOI: 10.1530/eje-16-0521
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density is increased after a 16-week resistance training intervention in elderly women with decreased muscle strength

Abstract: Our findings suggest an important role of continuous supervised resistance training for the prevention of osteoporotic fractures in elderly women with decreased muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
2
23
0
3
Order By: Relevance
“…Several studies have investigated the effect of exercise on bone turnover markers in serum in non‐OA individuals, however, with varying results . In agreement with our study, resistance exercise combined with or without impact loading was without effect on CTX and PINP, However, soccer training increased PINP and CTX levels in non‐OA individuals suggesting that the type of exercise is relevant for the effect on bone turnover. The lack of effect of exercise on PINP and CTX in our study could therefore be due to the type or duration of exercise but could also be the result of altered bone turnover in OA patients.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have investigated the effect of exercise on bone turnover markers in serum in non‐OA individuals, however, with varying results . In agreement with our study, resistance exercise combined with or without impact loading was without effect on CTX and PINP, However, soccer training increased PINP and CTX levels in non‐OA individuals suggesting that the type of exercise is relevant for the effect on bone turnover. The lack of effect of exercise on PINP and CTX in our study could therefore be due to the type or duration of exercise but could also be the result of altered bone turnover in OA patients.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the authors of above study obtained convergent results to ours. Huovinen et al [30] analyzed the effects of resistance training on the elderly patients with reduced muscle strength. After 16 weeks of intervention a significant increase in sclerostin and OC was noted, unlike the other markers (CTX and PINP).…”
Section: Prace Oryginalnementioning
confidence: 99%
“…These studies encompassed a varied population as to age, sex and training protocols, using only resistance exercises, but with different loading intensities, with the exception of the Petersen et al 24 study, which included exercise for cardiovascular endurance on a bicycle. For Petersen et al 24 , the use of low loads (20% 1-RM) associated to the high number of repetitions showed similar effectiveness to other studies that employed intensity between 50-95% 1-RM 21,32 . Additionally, the study of Almstedt et al 32 which analyzed the alterations by sex, indicated that among men the effects were more pronounced.…”
Section: Effects Of Resistance Training On Body Composition Muscle Smentioning
confidence: 68%
“…The studies highlighted in Boards 1 and 2 provide updated results corroborating the effects of RT on bone remodeling. Studies that showed a greater effect of RT on BMC/BMD reported changes between 6 and 8% 21,22,32 . These studies encompassed a varied population as to age, sex and training protocols, using only resistance exercises, but with different loading intensities, with the exception of the Petersen et al 24 study, which included exercise for cardiovascular endurance on a bicycle.…”
Section: Effects Of Resistance Training On Body Composition Muscle Smentioning
confidence: 99%
See 1 more Smart Citation